2006
DOI: 10.1161/01.str.0000202582.29510.6b
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Basilar Artery Occlusion

Abstract: Background and Purpose-Basilar artery occlusion (BAO) is an infrequent form of acute stroke, which invariably leads to death or long-term disability if not recanalized. A traditional recanalization approach based on historical controls and pathophysiological consideration is local intra-arterial thrombolysis (IAT) in eligible patients. This necessitates diagnostic evaluation and treatment in stroke centers equipped with an interventional neuroradiological service on a 24-hour basis, but its superiority to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
198
1
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(221 citation statements)
references
References 34 publications
11
198
1
11
Order By: Relevance
“…[13][14][15][16][17][18] The largest adult series, the Basilar Artery International Cooperation Study (BASICS), reported 619 patients with BAO of whom over half (328 of 619) received intra-arterial tPA and other mechanical endovascular treatments. Overall mortality was 39%, and 31% survived with an mRankin scale score of 4 or 5 for a 70% frequency of 'poor outcome' by the authors' definition.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] The largest adult series, the Basilar Artery International Cooperation Study (BASICS), reported 619 patients with BAO of whom over half (328 of 619) received intra-arterial tPA and other mechanical endovascular treatments. Overall mortality was 39%, and 31% survived with an mRankin scale score of 4 or 5 for a 70% frequency of 'poor outcome' by the authors' definition.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous administration has the theoretical advantage of easier access without the need for specialized interventional radiology set-up and reduced risk of haemorrhagic complications. 61,62 Its disadvantages include increased risk of causing direct vascular injury, increased risk of strokes, the requirement of a neurointerventionalist, and a longer procedural time. 56 An interventional case series showed significant visual improvement of three Snellen lines or more seen in patients treated with low-dose IA tPA (50 mg) within 6.5 h and concomitant intravenous heparin given to help prevent reocclusion.…”
Section: Acute Management Of Craomentioning
confidence: 99%
“…Although observational studies of urokinase and rt-PA for intra-arterial treatment of basilar artery occlusion have shown encouraging results, there are no randomized clinical trials with adequate statistical power [34][35][36] . A systematic review found no significant differences between intravenous or intra-arterial thrombolysis for basilar artery occlusion 37 . Recommendations 1) Intra-arterial thrombolytic therapy is a valid option to selecting patients with ischemic stroke due to MCA, carotid, or basilar artery occlusion if given in 6 hours after the stroke (Level of Evidence 2, Class B Recommendation) and, by extrapolation of the results of intravenous thrombolysis studies, rt-PA is used as the thrombolytic agent (Level of Evidence 4, Class C Recommendation).…”
Section: Protocol For Intra-arterial Thrombolysismentioning
confidence: 99%